Influence of home bleaching regimen on microhardness and flexural strength of two contemporary composite resins – an in vitro evaluation - Muralidasan Kalaivani; S Datta Prasad; M Indumathi; M Sruthipriya; Balachandran Janani; O Pavankumar (European Oral Research)
PurposeThis study was to compare and evaluate the effect of home bleaching on the microhardness and flexural strength of microhybrid and nanohybrid composite resins.Materials and MethodsThe study samples were prepared using a custom-made silicon rubber mold. For microhardness evaluation, 40 disc-shaped specimens (4mm*2mm) were prepared and divided into 4 groups: GROUP A (n=10): microhybrid (GC Solaire X, GC Corporation) control group, GROUP B (n=10) nanohybrid (Tetric N Ceram, Ivoclar Vivadent) control group, GROUP C (n=10): microhybrid bleaching group, GROUP D (n=10) nanohybrid bleaching group. For flexural strength evaluation, 40 bar shaped specimens (25mm*2mm*2mm) were prepared. They were divided into 4 groups, GROUP 1 (n=10): microhybrid control group, GROUP 2 (n=10) nanohybrid control group, GROUP 3 (n=10): microhybrid bleaching group, GROUP 4(n=10) nanohybrid bleaching group. All the control groups were placed in artificial saliva and bleaching groups were exposed to home bleaching agent for 14 days accordingto manufacturer’s instructions. The microhardness and flexural strength were evaluated for the respective specimens after 14 days and the data were statistically analyzed.ResultsHome bleaching regimen decreased microhardness of both microhybrid and nanohybrid composites whereas there was no significant effect on the flexural strength. Nanohybrid composites showed greater microhardness values before and after bleaching.ConclusionBleaching agents, irrespective of their concentration can decrease the microhardness of the composite resin samples, which raises a concern about replacement of these restorations due to the effects on physical and mechanical properties.